2009
DOI: 10.1097/sla.0b013e3181a38f6f
|View full text |Cite
|
Sign up to set email alerts
|

Surgeon Characteristics and Use of Breast Conservation Surgery in Women With Early Stage Breast Cancer

Abstract: Background Most women with localized breast cancer (BC) have a choice between mastectomy and breast conserving surgery (BCS). Aside from clinical factors, this decision may be associated with surgeon and patient characteristics. We investigated the effect of surgeon characteristics on the BCS rate. Methods We used the SEER-Medicare database to identify women >65 years, diagnosed with stages I-II BC, between 1991–2002, and used the Physician Unique Identification Number linked to the American Medical Associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
56
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(63 citation statements)
references
References 36 publications
4
56
2
Order By: Relevance
“…Higher-volume surgeons were also much more likely to correctly perceive that the quality of life at 1 year is higher for women who receive BCS than for women who received a mastectomy (47.2 % for low-volume surgeons vs 65.4 % for high-volume surgeons; Wald test=27.5; P<0.001) [9]. Similar results have been found by others and demonstrate the ability of specialists to appreciate the multidisciplinary impact that a mastectomy has on women [10][11][12][13][14].…”
Section: Patient Satisfaction and Quality Of Lifesupporting
confidence: 86%
“…Higher-volume surgeons were also much more likely to correctly perceive that the quality of life at 1 year is higher for women who receive BCS than for women who received a mastectomy (47.2 % for low-volume surgeons vs 65.4 % for high-volume surgeons; Wald test=27.5; P<0.001) [9]. Similar results have been found by others and demonstrate the ability of specialists to appreciate the multidisciplinary impact that a mastectomy has on women [10][11][12][13][14].…”
Section: Patient Satisfaction and Quality Of Lifesupporting
confidence: 86%
“…Surgeon and hospital factors may also play a role. Surgeon preferences, surgeon and hospital volume and hospital teaching status have been found to be associated with type of surgery and may also be associated with survival [22][23][24]. Further investigation into these factors is merited, as results may have potential for policy implications.…”
Section: Discussionmentioning
confidence: 99%
“…Higher surgeon case load has repeatedly been associated with improved surgical outcomes. 28,29 Subspecialty surgical training was also associated with surgical outcomes in one study. 30 In the current study, we found a consistent association between provider volume and use of newer chemotherapy drugs.…”
Section: Discussionmentioning
confidence: 99%